Systems Engineering Value Stream Modelling. Issue 1 (2014) - Scheithauer, Dieter
Abstract The V‐Model denotes the overall systems engineering value stream. The value stream consists of configuration baselines referencing the information handed over across the system architecture for top‐down design and bottom‐up integration. In addition, system integration preparation is depicted by direct flows from the left leg to the right leg of the V for each system. In order to exploit the full power of value stream thinking, the value streams for the generation of each particular configuration baseline have to be considered. This paper justifies the precedence of the value steam approach compared to document centred and process oriented approaches applied to particular documents. Configuration management in systems engineering is adjusted with respect to the value stream based approach. The process definition model for defining the value streams for generating individual configuration baselines is fully described. The paper concludes with considerations how to establish these work product generation sequences in practice.